Approaches to Develop the Herbal City for Health Tourism in Samutprakan Province - Pitivorayuth, Prayuk (Interdisciplinary Academic and Research Journal, 2023)
The situation of herbs abroad and in Thailand is growing a lot from the trend of people’s health consciousness. As a result, medical tourism is very popular among tourists. which the Thai government attaches importance to medical tourism by establishing a policy to promote and push Thailand to be a center of health (Medical Hub) of international countries, there are 13 herbal cities targeted areas, with the western part of Samut Prakan province being one of the targeted provinces. due to the availability of resources but in practice, there is still a problem in implementing the policy into practice. At present, there is no concrete result from policy propulsion. This research has therefore studied the development of herbal towns for health tourism in Samut Prakan Province. 1) to study the application of health tourism development policies. 2) to study the readiness of tourist attractions and tourism services for the health tourism destination "Herb City" in the area of Samut Prakan Province and 3) to study guidelines for the development and management of health tourism. "Herb City" in Samut Prakan Province This research is qualitative. The results of the study revealed that the implementation of the health tourism development policy "City of Herbs" to practice in Samut Prakan Province The medical tourism committee has not yet been established. There should be an integration of collaboration between various sectors, including the public sector, the private sector, and network partners. Problems and obstacles are Insufficiency of herbs, equipment, and knowledge. As for the success factors in implementing medical tourism policies "City of Herbs" into action in Samut Prakan Province government policy setting Department of Traditional Thai Medicine The province has determined the development of herbal towns to drive operations to meet the needs of the people. Not much acceptance and practice There is no provincial public health office committee established. Policy options should be integrated. Policy Awareness Creation Little awareness of the policy the province creates awareness in some government agencies that do not cover the people. on the actual effect during the implementation of the policy, Central must set clear policies, roles, and responsibilities. Executives see the importance of creating careers and people’s income. The availability of tourist attractions and tourism services for health tourism destinations is convenient to access facilities are sufficient the tourist attractions are diverse. service the public participated in the service provision. development and Management approach "Herbal City" for health tourism in Samut Prakan Province There should be a central, provincial, and local committee to establish and organize a committee of herbal towns and health tourism destinations. promote people Create network partners to drive concrete.